Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada PT. Sumber Alfaria Trijaya, tbk (alfamart talang kelapa 2) - Debby Marthalia; Kemas Welly Angga Permana; Tutik Pebrianti; Indah Mawarni; Sri Sutandi (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This study aims to determine: The effect of service quality on customer satisfaction at PT. Sumber Alfaria Trijaya, Tbk (Alfamart Talang Kelapa 2). This research is categorized as asositive research. The type of data in this study is quantitative data or in the form of numbers. The research instrument used a questionnaire. The population in this study are consumers at PT Sumber Alfaria Trijaya, Tbk. The sampling technique in this study uses non-probability sampling. The instrument validity test uses Confirmatory Factor Analysis while the reliability test uses Cronbach Alpha. The measuring instrument is valid and reliable for research instruments. Multiple regression analysis was used to test the hypothesis of this study. The results of the study at a significance level of 5% found that: (1) service quality has a positive effect on customer satisfaction at PT. Sumber Alfaria Trijaya, Tbk (Alfamart Talang Kelapa 2) hereby that the value of t arithmetic is 4.381 while the value of t table is 0.2423 besides the significance value also indicates the value of 0.002 is smaller than the alpha value of 0.05. (2) service quality has a positive effect on customer satisfaction at PT. Sumber Alfaria Trijaya, Tbk (Alfmart Talang Kelapa 2) with a calculated value of 4.381 while the value of t table (n = 66, α = 5%) amounted to 0.2423.